SiC 하이브리드 모듈을 적용한 근거리용 7kW Inverter 동작 안정성에 대한 연구 - 전준혁(Joon-Hyeok Jeon); 경신수(Sin-Su Kyoung); 김희준(Hee-Jun Kim) (한국정보전자통신기술학회 논문지, 2019)
This paper is concerned with the operating stability of 7kW inverter using SIC hybrid module and verifies the validity of the simulation results by comparing the result of the loss equation and the simulation result, Simulation results using Si module and SiC hybrid module are compared to compare switch loss and diode loss. Through the loss equation calculation, the conduction loss of SiC Hybrid module is 168W, switching loss is 9.3W, diode loss is 10.5nW, When compared with the simulation results, similar values were shown. As a result of comparing the simulation results of the Si module and the SiC Hybrid module, The total device loss of the Si module was 246.2W, and the total device loss of the SiC Hybrid module was 189.9W. The loss difference was 56.3W, which was about 0.8W. thereby verifying the reverse recovery characteristics of the SiC SBD. In addition, temperature saturation test was conducted to confirm the stability of SiC Hybrid module and Si module under high temperature saturation, In the case of the Si module, the output power was stopped at 4kW, and the SiC Hybrid module was confirmed to operate at 7kW. Based on this, an efficiency graph and a temperature graph are presented, and the Si module is graphed up to 4kW and the SiC Hybrid module is graphed up to 7kW. 본 논문은 SiC Hybrid module를 적용한 7kW 인버터의 동작 안정성에 관한 것으로 손실 방정식과 시뮬레이션 결과를 비교하여 시뮬레이션 결과의 유효성을 검증하였으며, 시뮬레이션을 통해 Si module과 SiC Hybrid module의 스위치 손실과 다이오드 손실을 비교하였다. 손실 방정식 계산을 통하여 SiC Hybrid module의 도통 손실은 168W, 스위칭 손실은 9.3W, 다이오드 손실은 10.5nW의 결과를 나타내었으며, 시뮬레이션 결과와 비교하였을 때 유사한 값을 나타내었다. 이를 바탕으로 Si module과 SiC Hybrid module의 시뮬레이션 결과 값 비교 결과, Si module의 총 소자 손실값은 246.2W, SiC Hybrid module의 총 소자 손실 값은 189.9W를 나타내었으며, 손실 차이 값은 56.3W로써 약 0.8W의 효율 차이를 보였다. 이로 인하여 SiC SBD의 Reverse recovery 특성을 검증하였다. 또한 고온 포화상태에서 SiC Hybrid module 및 Si module의 안정성을 확인하기 위하여 온도 포화 테스트를 진행하였으며, Si module의 경우, 출력전력 4kW에서 동작을 멈추었고, SiC Hybrid module은 7kW까지 동작을 확인하였다. 이를 바탕으로, 효율 그래프와 온도 그래프를 제시하였으며, Si module은 4kW까지, SiC Hybrid module은 7kW까지 그래프로 나타내었다.